Effects of Electrical Stimulation on Meat Quality of Lamb and Goat Meat - Omer Cetin; Enver Baris Bingol; Hilal Colak; Hamparsun Hampikyan (The Scientific World Journal)
Effect of various voltage of electrical stimulation (ES) on meat quality of lamb and goat was investigated by using a total of 36 animals at 3–5 years old. Constant 50 Hz frequency and 50, 100, and 250 V, 90 sec of ES were administered to 1/2 carcasses and were examined according their textural, physicochemical, and sensorial characteristics. ES decreased the pH values of lamb and goat meat, and accelerated the rigor mortis (𝑃<0.05). Additionally, ES enhanced the water activity, water-holding capacity, and drip loss of both animals. Shear force varied between lamb and goat meat, and tenderness was improved depending on voltage range used (𝑃<0.001). ES caused difference in instrumental colour (CIE 𝐿∗, 𝑎∗, 𝑏∗) values of lamb and goat meat compared with the control groups (𝑃<0.05) during aging period at 4°C. Sensorial characteristics were also improved with various levels of ES treatments. In conclusion, ES had positive effects on meat quality of lamb and goat, in contrast to undesirable consumer preferences.